Top management team functional diversity and organizational innovation in China: The moderating effects of environment. (28th May 2012) - Qian, Cuili; Cao, Qing; Takeuchi, Riki
Abstract While conflicts (cognitive and affective) have been considered as important process variables to better understand the mixed findings on the relationship between top management team functional diversity and organizational innovation, such an input‐process‐outcome model is still incomplete without considering the environmental factors. This study was formulated to assess the importance of both competitive and institutional environments in moderating such upper echelon effects within a transition economy. The chief executive officers and chief technology officers of 122 Chinese firms were surveyed and both competitive uncertainty and institutional support were found to shape top management team decision making processes and their outcomes. Copyright © 2012 John Wiley & Sons, Ltd.